Peran Pondok Pesantren dalam Membangun Pendidikan Islam Multikultural pada Masyarakat Pesisir - Sultoni, Agus (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
The understanding of plurality and diversity is a necessity that must be carried out and followed up deeper, especially in the scope of community, nation and state. One of the portraits of Islamic education that the author describes is the role of Islamic boarding schools located on the coast, because in this coast there is generally a multi-cultural and religious side by side. As we know that coastal communities have a form of community patterns with their cultural context and the ability to preserve it in the midst of various waves of change through the process of acculturation and syncretization. This paper is intended to explain descriptively the analysis of what and how the patterns were formed. In short, that coastal Islamic education is one of the conditioning icons amid the multidimensional warming temperatures caused by the domain of the majority community - borrowing the term Geertz is - abangan.